2011
DOI: 10.1080/19475411.2011.592866
|View full text |Cite
|
Sign up to set email alerts
|

Review on the temperature memory effect in shape memory alloys

Abstract: Shape memory alloys (SMAs) are well known for their unique shape memory effect (SME) and superelasticity (SE) behavior. The SME and SE have been extensively investigated in past decades due to their potential use in many applications, especially for smart materials. The unique effects of the SME and SE originate from martensitic transformation and its reverse transformation. Apart from the SME and SE, SMAs also exhibit a unique property of memorizing the point of interruption of martensite to parent phase tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…It is well known that many copper alloys such as CuAl, Cu-Zn-Al, Cu-Al-Ni and Cu-Al-Mn exhibit shape memory properties [5][6][7] . Cu-based SMAs have attracted much attention due to their good shape memory capacity, narrow temperature region of transformation, ease of fabrication and low production cost 8 . For the alloys of the ternary Cu-Zn-Al system, the shape memory effect is only observed within a certain range of composition which generally contains 16 to 30% of Zn and 4 to 8% of Al 3 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that many copper alloys such as CuAl, Cu-Zn-Al, Cu-Al-Ni and Cu-Al-Mn exhibit shape memory properties [5][6][7] . Cu-based SMAs have attracted much attention due to their good shape memory capacity, narrow temperature region of transformation, ease of fabrication and low production cost 8 . For the alloys of the ternary Cu-Zn-Al system, the shape memory effect is only observed within a certain range of composition which generally contains 16 to 30% of Zn and 4 to 8% of Al 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The question arises when a multistage MT is present. Previous works have undoubtedly found the TME in the B19 →R transformation, but it is not so clearly present in the R→Austenite transformation [26]. This seems to be due to the low calorimetric signal of this last transformation.…”
Section: Introductionmentioning
confidence: 73%
“…It has also been found that after a complete reverse MT, all these effects are erased. In the last few years, various interpretations have been proposed to explain the TME, which seems to be present in most SMAs and related to the relaxation of the elastic strain energy of the martensitic variants [26,28]. In the case of TiNi alloys, some qualitative descriptions have been developed in which the role of the elastic energy, dislocations, and grain boundaries are also discussed [26,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Fig.7 form [13], on TiNiCu thin films or Fig.2 form [14] on MiMnGa based bulk alloys) may be interpreted as evidence of memory fading by heating to lower temperatures, but have not been given this particular interpretation. …”
Section: Introductionmentioning
confidence: 99%